The Effect Of Workload, Organizational Culture And Work Discipline On Employee Work Productivity At CV. Medan Baru - Deharu, Rommy; Federori, Jodi (Journal Boas : Business, Economics, Accounting And Management, 2024)
Every organization continuously strives to ensure that its members or employees contribute to achieving maximum work productivity, aligning with predetermined goals. Work productivity is crucial in a bureaucratic setting, as it enables tasks to be completed effectively and efficiently, ultimately supporting goal achievement. One factor influencing employee productivity is workload, as assigned tasks may not always match their skills and expertise. Establishing an organizational culture is a complex and ongoing process, as cultural values and norms evolve over time. Additionally, a high level of discipline is essential for achieving organizational goals. Employees are expected to maintain strong discipline in fulfilling their responsibilities, which in turn enhances productivity. This study involved 93 respondents using a saturated sampling technique. The analysis was conducted using multiple linear regression. The findings indicate that workload, organizational culture, and work discipline collectively have a significant impact on employee productivity. However, while organizational culture and work discipline significantly influence productivity, workload does not have a notable effect.